2015
DOI: 10.1097/mib.0000000000000331
|View full text |Cite
|
Sign up to set email alerts
|

MyD88 Mediates the Protective Effects of Probiotics Against the Arteriolar Thrombosis and Leukocyte Recruitment Associated with Experimental Colitis

Abstract: Several studies in IBD patients and in animal models of IBD have revealed a protective effect of probiotics in reducing clinical symptoms of disease and in blunting the gut inflammation that accompanies this condition. However, the mechanism underlying the therapeutic effect of probiotics is currently unknown. Furthermore, the ability of probiotics to influence the enhanced thrombus development that accompanies IBD has not been studied. This study addresses whether the enhanced extra-intestinal thrombosis (ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…As previously reported, thinner colonic mucus was found in patients with UC, as well as in mouse and rat models of colitis, compared with controls (Petersson et al, 2011; Dicksved et al, 2012; Johansson et al, 2014). Furthermore, multiple studies have revealed that intestinal permeability and LPS levels were increased in mice with colitis (Souza et al, 2015; Llewellyn et al, 2018), these findings suggested intestinal barrier damage and sequentially aggravated intestinal colitis. Importantly, A. muciniphila , identified as a mucin-degrading bacteria (Derrien et al, 2004), could continuously reshape and refresh the mucus layer, thereby creating a healthy environment for epithelial cells and maintaining the integrity of the intestinal barrier (Everard et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As previously reported, thinner colonic mucus was found in patients with UC, as well as in mouse and rat models of colitis, compared with controls (Petersson et al, 2011; Dicksved et al, 2012; Johansson et al, 2014). Furthermore, multiple studies have revealed that intestinal permeability and LPS levels were increased in mice with colitis (Souza et al, 2015; Llewellyn et al, 2018), these findings suggested intestinal barrier damage and sequentially aggravated intestinal colitis. Importantly, A. muciniphila , identified as a mucin-degrading bacteria (Derrien et al, 2004), could continuously reshape and refresh the mucus layer, thereby creating a healthy environment for epithelial cells and maintaining the integrity of the intestinal barrier (Everard et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…A previous study also observed that the expression of genes associated with the immune response was increased by A. muciniphila colonization (Derrien et al, 2011). Cytokines such as TNF-α and IL6 were highly expressed in humans with IBD (Reinecker et al, 1993) and experimental models of IBD (Yoshida et al, 2011; Senchenkova et al, 2013; Yan et al, 2014), and interventions to block their accumulation could protect against colitis (Souza et al, 2015). Moreover, these cytokines have been found to be involved in the disruption of epithelial tight junctions through the NF-κB signaling pathway, resulting in mucosal dysfunction (Fink, 2003; Ahl et al, 2016; Woodhouse et al, 2018; Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Based on accumulating evidence, epithelium destruction and a severe inflammatory response occur in patients with IBD (Souza et al , 2005; Coskun, 2014). Similarly, the damaged intestinal epithelium induced by the administration of DSS results in increased exposure of immune cells to antigens, consequently inducing a profound immune response (Souza et al , 2015; Llewellyn et al , 2018). In the present study, the P. pentosaceus LI05 treatment exerted protective effects on colonic inflammation by decreasing the levels of the cytokines and chemokines IL1α, IL6, TNF‐α and MIP‐1A, increasing the level of the anti‐inflammatory cytokine IL10 and reducing neutrophil infiltration in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics are living microbes that exert a demonstrated beneficial effect on human health if administered at effective doses. Probiotics have been found to protect against colitis in both experimental models and human studies (Bibiloni et al , 2005; Souza et al , 2015; Ahl et al , 2016). Genera such as Lactobacillus , Faecalibacterium and Akkermansia exert anti‐inflammatory effects on the intestinal mucosa of patients with IBD (Tamboli et al , 2004; Sokol et al , 2009; Bian et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…While the precise mechanism of action remains to be investigated, the susceptibility of MyD88-deficient mice to colitis has been linked to gut microbiota composition, which is altered in IBD (36). Furthermore, MyD88 -/mice, in contrast with wild-type mice, are unable to respond to treatment with probiotic bacteria in the context of DSS-induced colitis, further highlighting the link between MyD88 and the gut microbiota (50). Overall, the implications of these studies are that bacterial components may play both detrimental (36) and protective roles, at least partially, in a MyD88-dependent manner (1,50).…”
Section: Discussionmentioning
confidence: 99%